High shear strength welding of soda lime glass to stainless steel using an infrared nanosecond fiber laser assisted by surface tension. (February 2023) - Li, Chuangkai; Tan, Juntao; Luo, Minghuo; Chen, Wenjun; Huang, Yanxin; Gu, Jialei; Zhao, Nan; Li, Jiaming; Yang, Huan; Zhang, Qingmao
Highlight: Glass and metal were bonded and then welded together using ns-laser assisted by interstitial fluid surface tension without clampers. A pre-welding method was proposed to expand available range of laser welding parameters. A maximum shear strength of 9.74 MPa and RSD of 5.3% was obtained with a ns-laser, even higher than previous reported works using ultrafast lasers. Abstract: High shear strength laser welding of glass-to-metal connections are significant in various areas. However, ultrafast laser processing methods are high cost and demanding, while nanosecond laser processing requires clampers to make samples in optical contact. This work proposed an efficient approach based on liquid surface tension in ns-laser welding. Steel and glass were stably bonded together by the surface tension of the interstitial fluid and kept within optical contact (<200 nm). The two materials were welded successfully using a nanosecond fiber laser and the maximum shear strength of 9.74 MPa with a relative standard deviation of 5.3% was obtained. Meanwhile, the welding mechanism was discussed. Furthermore, a pre-welding method, expanding the available parameters range in nanosecond laser welding, was also investigated to stabilize the optical contact condition for a long time. This work provides a convenient approach for improving efficiency and reliability in laser welding industry.